Exploring factors influencing Thai autonomous vehicle acceptance: A grounded theory approach - Sithanant, Thana; Chaiyasoonthorn, Wornchanok; Chaveesuk, Singha (Edelweiss Applied Science and Technology, 2025)
This research explores factors influencing consumer acceptance of autonomous vehicles (AVs) in Thailand, where local culture, infrastructure, and habitual behaviors are essential factors often overlooked in regional studies. Most previous research on AV acceptance has employed quantitative methods and focused on Western, developed contexts. This study aims to develop a framework for AV adoption incorporating contextually relevant factors, utilizing the qualitative grounded theory approach. Data were collected through 24 semi-structured interviews with AV owners in Thailand. An iterative analysis process involving three stages, open, axial, and selective coding, resulted in the identification of 19 categories. These categories were integrated into five overarching themes: (1) vehicle characteristics, (2) customer experience and support, (3) user-related factors, (4) financial aspects, and (5) external support mechanisms, which influence AV acceptance. The findings indicate that while many existing technology acceptance constructs are applicable, their interaction with indigenous factors such as trust in established brands, congested traffic conditions, and the need for post-purchase education and support is crucial in the Thai context. A comprehensive framework summarizing these findings is proposed, emphasizing the contingent, multi-dimensional, and nuanced nature of AV diffusion in emerging economies. The model provides a foundation for future quantitative validation and offers practical insights for policymakers, manufacturers, and researchers to facilitate AV adoption in Thailand and similar developing regions.